CURRICULUM REFORM AND LEARNING NEEDS IN ISLAMIC EDUCATION: AN ANALYSIS OF THE MERDEKA CURRICULUM IMPLEMENTATION AT MI AL-AWWAL PALEMBANG - Mizan, Muhammad; Putri, Inka Rizka Amalia; Dewi, Nurmala; Lestari, Nastiti Puji; Afriantoni (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study analyzes the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) at MI Al-Awwal Palembang, with a particular focus on how the curriculum reform addresses the actual learning needs of students in the context of Islamic education. Employing a qualitative case study approach, data were collected through classroom observations, teacher and student interviews, and analysis of instructional documents. The findings reveal that the curriculum implementation has generally been effective, supported by well-developed instructional tools, diverse teaching methods, and conducive classroom environments. Nonetheless, several challenges persist, including the limited integration of digital learning media, inconsistent student engagement, and a lack of authentic assessment that reflects the spiritual and moral dimensions of Islamic education. This study contributes to the ongoing discourse on curriculum reform in Islamic elementary education and offers practical recommendations for aligning the Merdeka Curriculum more effectively with the religious and academic learning needs of students. Penelitian ini menganalisis implementasi Kurikulum Merdeka dalam pembelajaran Pendidikan Agama Islam (PAI) di MI Al-Awwal Palembang, dengan fokus pada bagaimana reformasi kurikulum tersebut menjawab kebutuhan belajar peserta didik dalam konteks pendidikan Islam. Pendekatan studi kasus kualitatif digunakan dengan teknik pengumpulan data melalui observasi kelas, wawancara dengan guru dan siswa, serta analisis dokumen pembelajaran. Hasil penelitian menunjukkan bahwa implementasi kurikulum secara umum telah berjalan efektif, ditunjang oleh perangkat ajar yang terstruktur, metode pengajaran yang bervariasi, dan suasana kelas yang mendukung pembelajaran. Namun, masih terdapat tantangan, antara lain keterbatasan pemanfaatan media pembelajaran digital, keterlibatan siswa yang belum konsisten, serta kurang optimalnya penerapan penilaian autentik yang mencerminkan dimensi spiritual dan moral dalam pendidikan Islam. Penelitian ini memberikan kontribusi terhadap diskursus reformasi kurikulum pada pendidikan dasar Islam serta menawarkan rekomendasi praktis untuk menyelaraskan Kurikulum Merdeka dengan kebutuhan belajar religius dan akademik peserta didik.